Flashback: Vehicles & Traffic - Språkbanken Text (University of Gothenburg, 2025)
Material from the Flashback internet forum.

Material från diskussionsforumet Flashback.
Flashback: Fordon & trafik
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik